Does the money multiplier hold in Pacific Island countries? The case of Papua New Guinea - Mark Ofoi; Parmendra Sharma (Journal of Risk and Financial Management, 2021)
This is the first study to systematically assess the significance of the standard money multiplier vis-à-vis the bank credit transmission channel in the case of Pacific Island Economies, focusing on Papua New Guinea. The vector autoregressive model comprising six variables - interest rate, inflation rate, loans, deposits, reserve money, and real output - was estimated using quarterly data for the period 1980q1 to 2017q4. We applied the ordinary least squares (OLS) method to estimate the system of vector autoregressions (VARs). The estimation was conducted for the full and sub-sample periods. From the impulse response functions generated, the results suggest that the money multiplier does not hold and that the transmission to bank credit appears weak. It seems that the ability of the Central Bank to make loanable funds available through its conduct of monetary policy may not enhance private sector credit. On the other hand, there appears to be a significant and positive association between bank deposits and credit, suggesting that bank deposits and credit are endogenous and demand driven.
Keywords: 330; monetary policy; bank credit; money multiplier; reserve money